BARRIER FACED BY SMES TO ADOPT DIGITAL MARKETING: SPECIAL REFERENCE TO UTTAR PRADESH - Pradhan, Priyanka; Nigam, Devesh; Tewari, C.K. (International Journal of Psychosocial Rehabilitation, 2020)
In the 21st century, where the world is driven by technology, digitalization plays a really vital role in running a trade in order to maximize the benefit and make a mark in the developing trade industry. SMEs (Small-Medium Enterprises) are the backbone of the economy in India and thus it becomes imperative for them to change with digitization and adopt different digital marketing tools for their business. While adopting these tools to enhance their performance many SMEs have failed or improperly adopted the digital marketing. Through this research paper we will be highlighting challenge that SMEs in Uttar Pradesh have to face while adopting digital marketing. The objectives of the study are an investigation of barriers to adopt digital marketing tools by SMEs of Uttar Pradesh and testing the significance of these barriers with digital marketing adoption in context to SMEs of Uttar Pradesh. ANOVA and rating system based on Mean Score were used to identify and test significance of these barriers. All the barriers identified have significant relationship with digital marketing adoption. Lack of skilled ICT, Inadequate information and resistance to change were identified as potential barrier while adopting digital marketing. Implications for future, more quantitative studies are required to help the SMEs to adopt new technologies and how to avoid face the hurdles in order to achieve profitability.